UX aspects of interaction with a system of collaborative cleaning robots: A speculative design study investigating how interaction with a system of mobile and collaborative cleaning robots should be designed to support the users’ experience during configuration and operation - Grafström, Anna; Holmgren, Moa (My University, 2022)
The possibility of developing a system of mobile and collaborative cleaning robots to assist human workers with the cleaning of food plants is currently under investigation. This master’s thesis aims to identify the future key users of a robot system, and takes a speculative design approach to investigate how the interaction with this system could be designed to support a good User Experience in the future 10 years from now. To gain an understanding of the system of robots and the intended users, their tasks, and the food plant context, the focus was initially put on user studies and data gathering. Two key user roles could be defined: system configurators and system operators. Thereafter, the interaction between the key users and the robot system was explored. Regarding system configuration, a suggestion on how a system configuration procedure could look in the future was developed and presented using a Hierarchical Task Analysis. Regarding system operation, four different speculative interaction design concepts were developed and presented using storyboards. The Hierarchical Task Analysis and the storyboards were subsequently evaluated with intended future key users, designers, and stakeholder companies. Finally, 11 design recommendations for interaction design could be derived. Cases exemplifying a speculative design concept for interaction design based on these recommendations were also further demonstrated through two future scenarios.
Keywords: Interaction Design; User Experience; Human-Robot Interaction; Human- Robot Collaboration; Speculative Design; System Configuration; Industrial Cleaning; Food Industry